2002
DOI: 10.1007/s00122-002-1170-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular linkage maps of Vitis vinifera L. and Vitis riparia Mchx

Abstract: Two linkage maps for grape (Vitis spp.) have been developed based on 81 F(1) plants derived from an interspecific cross between the wine cultivar Moscato bianco (Vitis vinifera L.) and a Vitis riparia Mchx. accession, a donor of pathogen resistance traits. The double pseudotest-cross mapping strategy was applied using three types of molecular markers. The efficiency of SSRs to anchor homologous linkage groups from different Vitis maps and the usefulness of AFLPs in saturating molecular linkage maps were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 42 publications
9
67
2
Order By: Relevance
“…This is higher than that reported by Troggio et al (2007) and Grando et al (2003), but lower than the 40 % reported by Riaz et al (2011). One region of distortion that stood out was chromosome 15 where all 13 markers showed significant segregation distortion as previously reported for 'Regent' in this region by Welter et al (2007).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This is higher than that reported by Troggio et al (2007) and Grando et al (2003), but lower than the 40 % reported by Riaz et al (2011). One region of distortion that stood out was chromosome 15 where all 13 markers showed significant segregation distortion as previously reported for 'Regent' in this region by Welter et al (2007).…”
Section: Discussioncontrasting
confidence: 49%
“…Additional to this major locus, two minor loci were identified on chromosomes 5 and 20, but were not assigned specific names. Several genetic maps have been constructed for grapevine (Dalbó et al 2000;Doligez et al 2002;Grando et al 2003;Adam-Blondon et al 2004;Fischer et al 2004;Riaz et al 2004;Doligez et al 2006;Lowe and Walker 2006;Di Gaspero et al 2007;Troggio et al 2007;Welter et al 2007;Vezzulli et al 2008;Bellin et al 2009;Marguerit et al 2009;Moreira et al 2011;Blasi et al 2011;Blanc et al 2012). The first maps were constructed using mainly AFLP and RAPD markers.…”
Section: Powdery Mildewmentioning
confidence: 99%
“…Primer pairs for VVMD microsatellites were published in Bowers et al (1996) and Bowers et al (1999b); for VrZAG in Sefc et al (1999); for VVS in Thomas and Scott (1993) and Thomas et al (1998). All 60 markers were already mapped (Grando et al, 2003;Riaz et al, 2004) and they have been chosen in 18 out of the 19 linkage groups of the grape genome (Adam-Blondon et al, 2004), so that they are evenly distributed throughout the genome (average distance between the markers is 12 cM). The PCR mix was prepared in 10-ml volumes containing 0.2-3.0 ng of template DNA, 2-4 pmol of each forward and reverse primers, 1 Â PCR buffer, 2 mM MgCl 2 , 0.2 mM dNTPs and 0.5 U of HotStar Taq polymerase.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…'Pinot' and 'Syrah' are closely related JF Vouillamoz and MS Grando therefore suggest that 57 microsatellite markers should be a minimum for the detection of PO and FS pairs in grapes (without knowledge of both parents). As linkage maps are already available for grape cultivars (Grando et al, 2003;Riaz et al, 2004), the use of linked loci might help elucidating some competing relationship categories as their meiotic segregation patterns differ, but the power of these tests is low (see Blouin, 2003). Joint likelihood for trios of individuals might also help elucidating some relationships, but this method is rapidly computationally intensive.…”
Section: Fsmentioning
confidence: 99%
“…For mapping it would be necessary to involve large populations before any selection is done. Numerous markers have to be screened to get the mapping structure [15]. As an alternative strategy selection with chromosomal observation and definition of heritage was used to accelerate the breeding process.…”
Section: Introductionmentioning
confidence: 99%